2021
DOI: 10.1016/j.omtn.2021.07.020
|View full text |Cite
|
Sign up to set email alerts
|

circGNAQ, a circular RNA enriched in vascular endothelium, inhibits endothelial cell senescence and atherosclerosis progression

Abstract: Endothelial cell senescence is one of the most important causes of vascular dysfunction and atherosclerosis. Circular RNAs (circRNAs) are endogenous RNA molecules with covalently closed-loop structures, which have been reported to be abnormally expressed in many human diseases. However, the potential role of circRNAs in endothelial cell senescence and atherosclerosis remains largely unknown. Here, we compared the expression patterns of circRNAs in young and senescent human endothelial cells with RNA sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…48 Studies have shown that the expression of astrocyte lamina is significantly increased in the ischemic penumbra of MCAO mice. 49 COL4A is a member of type IV collagen family 50 and the most abundant basal lamina protein, 48 which participates in modulating cellular behaviors during the processes of tissue development, damage, and repair. For example, COL4A1 is considered as a monogenic cause of cerebral small vessel disease, including both ischemic stroke and intracerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…48 Studies have shown that the expression of astrocyte lamina is significantly increased in the ischemic penumbra of MCAO mice. 49 COL4A is a member of type IV collagen family 50 and the most abundant basal lamina protein, 48 which participates in modulating cellular behaviors during the processes of tissue development, damage, and repair. For example, COL4A1 is considered as a monogenic cause of cerebral small vessel disease, including both ischemic stroke and intracerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…The circular RNA circ_0003204 inhibits the proliferation, migration and tube formation of endothelial cells in atherosclerosis via the miR-370-3p/TGFβR2/phosph-SMAD3 axis [ 21 ]. circGNAQ was reported to inhibit endothelial cell senescence and atherosclerosis progression [ 22 ].However, the potential mechanism of circRNA on endothelium cells was rarely studied.…”
Section: Discussionmentioning
confidence: 99%
“…circGNAQ. Very recently, Wu et al correlated circGNAQ to the senescence of endothelial cells [288]. The levels of circGNAQ were reduced in senescent endothelial cells, as well as in aorta tissues from aged mice and in human blood samples from old people.…”
Section: Circular Rnas (Circrnas)mentioning
confidence: 99%
“…Further analyses demonstrated that circGNAQ sponges miR-146a-5p, which functionally affects the expression of polo-like kinase2 (PLK2), an enzyme implicated in cell cycle progression. Of interest, mice injected with circGNAQ showed reduced signs of atherosclerosis after the high fat diet [288].…”
Section: Circular Rnas (Circrnas)mentioning
confidence: 99%